Holocene Emergence of the South and East Coasts of Melville Island, Queen Elizabeth Islands, Northwest Territories, Canada - McLaren, P.; Barnett, D.M. (ARCTIC, 1978)
Twenty-five radiocarbon dates from the coast of Melville Island show that there has been up to 100 m of Holocene emergence. This evidence of post-glacial rebound suggests there was significant late-Wisconsin glacier cover on or near the island. The Winter Harbour moraine on the south coast is thought to mark the maximum northward advance of the Laurentide ice. However, emergence for this area appears to be essentially complete, whereas the northeast coast is still recovering at a rate of approximately 0.35 cm/yr. Ice cover in the region to the northeast must, therefore, have been thicker and/or lasted longer than in the peripheral areas of the Laurentide ice, lending support to the concept of an Innuitian Ice Sheet, rather than local ice masses over the central Queen Elizabeth Islands. Unfortunately, there is an absence of fresh glacial landforms and stratigraphy that can be attributed to the Innuitian Ice Sheet. We suggest that this ice sheet may have had a thermal regime below the pressure melting point, thus depriving the ice of much of its erosive and depositional capabilities, but with a sufficient mass to account for the observed pattern of emergence.